Targeted photodynamic therapy of glioblastoma mediated by platelets with photo-controlled release property. (November 2022) - Xu, Hua-Zhen; Li, Tong-Fei; Ma, Yan; Li, Ke; Zhang, Quan; Xu, Yong-Hong; Zhang, Yu-Cai; Zhao, Li; Chen, Xiao
Abstract: Photodynamic therapy (PDT) has recently emerged as a promising, targeted treatment modality for glioblastoma (GBM) which is the most vicious type of brain tumor. Successful GBM-PDT hinges upon light activation of a photosensitizer accumulated in the tumor. However, inadequate tumor accumulation of photosensitizer severely limits the success of PDT of GBM. To tackle this difficulty, we herein propose a drug delivery strategy of "platelets with photo-controlled release property". This strategy exploits platelets as carriers to deliver a photosensitizer which, in the current study, is a nano-composite (BNPD-Ce6) comprised of chlorine e6 (Ce6) loaded to boron nitride nanoparticles with a surface coating of polyglycerol and doxorubicin. To demonstrate the working mechanism and therapeutic advantage of this strategy, we loaded mouse platelets with BNPD-Ce6 to yield the nano-device BNPD-Ce6@Plt. In vitro experiments showed BNPD-Ce6@Plt to have a high loading capacity and efficiency. Laser irradiation (LI) at a wavelength of 808 nm induced ROS generation in BNPD-Ce6@Plt which displayed rapid activation, aggregation, and speedy discharge of BNPD-Ce6 into co-cultured GL261 mouse GBM cells which in turn, after LI, exhibited marked ROS generation, DNA damage, reduced viability, and cell death. In vivo animal experiments, mice that were intravenously injected with BNPD-Ce6@Plt exhibited rapid and extensive BNPD-Ce6 accumulation in both subcutaneous and intra-brain GL261 tumors shortly after LI of the tumors and the tumors displayed massive tissue necrosis after LI for a second time. Finally, a PDT regimen of two intravenous BNPD-Ce6@Plt injections each followed by multiple times of extracranial LI at the tumor site significantly inhibited the growth of intra-brain GL261 tumors and markedly increased the survival of the host animals. No apparent tissue damage was found in vital organs. Our findings make a compelling case for the notion that platelets are efficient carriers that can photo-controllably deliver nano-photosensitizers to achieve highly targeted and efficacious PDT of GBM. This work presents a novel approach to GBM-PDT with great translational potential. Graphical abstract: Image 1